2010
DOI: 10.2144/000113451
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry—based Metabolomics, Analysis of Metabolite-Protein Interactions, and imaging

Abstract: Our understanding of biology has been greatly improved through recent developments in mass spectrometry, which is providing detailed information on protein and metabolite composition as well as protein-metabolite interactions. The high sensitivity and resolution of mass spectrometry achieved with liquid or gas chromatography allows for detection and quantification of hundreds to thousands of molecules in a single measurement. Where homogenization-based sample preparation and extraction methods result in a loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 64 publications
1
44
0
2
Order By: Relevance
“…[8][9][10] Disease studies such as the fundamental understanding of the biochemistry of neurodegenerative diseases 11,12 or cancer, 13 drug distribution studies 10,14 and forensics, 15,16 among others, also benefit from the information revealed by MSI.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Disease studies such as the fundamental understanding of the biochemistry of neurodegenerative diseases 11,12 or cancer, 13 drug distribution studies 10,14 and forensics, 15,16 among others, also benefit from the information revealed by MSI.…”
Section: Introductionmentioning
confidence: 99%
“…DNA and associated proteins, which play an important role in gene regulation, gene- [44], IMS [144,147] Metabolomics tools MetabolomeExpress [150], metaP [151], KEGG [145], human metabolome project [142] Lipidomics methods MS [44,161], orbitraps [160], IMS [144,147] Lipidomics tools LIPID MAPS [165], XCMS [162], MZmine2 [163] environment interactions, development and in diseases such as inflammation and cancer [60,61]. Such modifications involve the DNA itself but not its sequence, i.e.…”
Section: Epigenomicsmentioning
confidence: 99%
“…Targeted strategies are specific and sensitive, allow absolute quantification and thus widely used in clinical diagnostics and drug development. Targeted approaches based on stable isotopes and models of metabolic networks allow estimation of the flux through biochemical pathways [145]. In contrast, untargeted approaches harbour a high coverage, though any metabolite identification is less specific and sensitive, and requires more intensive computational analysis.…”
Section: Metabolomicsmentioning
confidence: 99%
See 2 more Smart Citations